Cr(VI) Removal from Aqueous by Adsorption on Amine-Functionalized Mesoporous Silica Prepared from Silica Fume - Xitong Li; Caiyun Han; Wenjie Zhu; Wenhui Ma; Yongming Luo; Yang Zhou; Jie Yu; Kuixian Wei (Journal of Chemistry)
Amino-functionalized mesoporous silica MCM-41 materials have been prepared to develop efficient adsorbents of Cr(VI) in wastewater, using silica fume as silica source. Functionalization with amino groups has been carried out by using grafting method. The materials have been characterized by means of X-ray diffraction (XRD), nitrogen (N2) adsorption-desorption, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Adsorption potential of the material for Cr(VI) removal from aqueous solution was investigated by varying experimental conditions such as pH, initial metal concentration, and contact time. The equilibrium data were analyzed using the Langmuir and Freundlich isotherm by linear regression analysis, and the results show that the adsorption equilibrium data obeyed the Langmuir model. In addition, the kinetics analysis revealed that the overall adsorption process was successfully fitted with the pseudo-second-order kinetic model.